(untitled) (Fiep Bulletin - online, 2011)
Drawing is a global public heath problem requires politics enclosing risk factors to guarantee effective preventive measures. However, notification of drawing cases, affecting specially regions with poor death registration, making difficulty observation of relevant cases and consequently preventive measures. This article object`s is identified on literature risk factors for drowning and nursing teem participation on drowning prevention. Bibliographic investigation on LILACS, MEDLINE e CINAHL data bases using the keywords drowning", "risk factors" and "nursing".complete article, in last five years, writing in portuguese, english and Spanish. The most important risk factors for drowning: male gander, children between one and four yeas old, adults between 20 and 29 years old, alcohol associated with leisure activities. In this context, nursing has a important participation to disseminates preventives measures based on reality and nature of drawing. This investigation show`s the risk factors for drawing are children and adults, male gander and alcohol associated with leisure activities. In this way, are need to formulate public politics toward to identified danger environments together with preventive measures, to decrease number of drowning accidents.